Familiarity: Origins, trends, trends - Kolodnyj, Anatolij Mykolajovyč (Ukrai͏̈ns'ke relihijeznavstvo, 1996)
Familiarity creates its own specific continuum of spiritual life in Ukraine, becomes a notable phenomenon in the field of Ukrainian national revival. With this phrase, we identified a group of related phenomena in the spiritual life of present-day Ukraine, based on the idea of ​​a revival in one form or another of pre-Christian religion, which is considered by the organizers of the Homeland Movement as the authentic worldview of Ukrainians. It is impossible to call each of the currents of native religion a neo-religious denomination, because, first, some of them, by virtue of their belief-conceptions of monotheistic religions, do not accept such an assessment of themselves; and secondly, some of these trends are still not religiously determined, but exist at the level of some educational institutions, they appear in the form of peculiar clubs of interest; Thirdly, a number of them functions in a very limited religious space, consisting only of several communities and a relatively small number of followers.